A green and facile production of catalysts from waste red mud for the one-pot synthesis of glycerol carbonate from glycerol. Issue 1 (February 2019) - Das, Bikashbindu; Mohanty, Kaustubha
Graphical abstract: Highlights: Aluminum industry waste red mud was calcined and used as low-cost catalyst. Basic sites and basic strength of the catalysts varied with calcination temperatures. Highest glycerol conversion and glycerol carbonate yield achieved by catalyst calcined at 500 °C. Kinetic study and reaction mechanism of glycerol transesterification proposed. Catalyst calcined at 500 °C found to be resistant in presence of water-methanol as impurities. Abstract: In this study, waste red mud (RM) from aluminum industry was calcined at different temperatures between 400 °C–800 °C and was applied as catalysts for the efficient production of glycerol carbonate (GC) through transesterification of glycerol (GL) with dimethyl carbonate (DMC). No chemical pretreatments or incorporation of any other foreign active components into the surface of RM was performed before its application as a catalyst. XRD and FTIR analysis revealed that RM calcined at 500 °C (RM-500) possessed the maximum concentration of active NaAlO2 and Ca2 SiO4 sites, thus produced the highest catalytic activity (92.02% GC yield). At calcination temperature above 500 °C, hematite became the dominant phase and the concentration of NaAlO2 and Ca2 SiO4 decreased, which also decreased the catalytic activity. The RM-500 catalyst showed excellent resistant for the transesterification of GL in the presence of initial impurities like water and methanol. Based on the results of different characterization techniques, a plausible reaction mechanism and the deactivation mechanism was proposed. Further, the kinetic analysis and reusability study was also studied in details.